Retrospectiva e método de criação de instrumentos para o ensino de paisagismo - Silva, Jonathas Magalhães Pereira da (Paisagem e Ambiente, 2002)
The speed of present day technological development demands and inspires new ways of communication and work. The incorporation of these new technologies in the educational agenda may not only ease and speed up learning but also contribute to the discussion of new academic programs and contents. The role of new technologies in education should be clearly established and their goals well defined before the development of new teaching tools begins. It is necessary to adopt strategies that allow educators to establish these preconditions; they do not need any technical knowledge, but must see where and how we can use these technological improvements. In landscape teaching there are permanent challenges inside the classroom, as for instance: the dealing with many project scales, a lack of open-space repertoire and three-dimensional vision, the structuring and articulation of the different spaces of a project. The objective of this paper is to discuss the methods used to develop the tools described above, as well as to present its actual uses and future development.